Straightforward Synthesis of BHQ-3 Amine: An Azo Dark-Quencher for FRET-Based Protease Activity Assays - Cátia D. F. Martins; Maria Manuela M. Raposo; Susana P. G. Costa (Chemistry Proceedings, 2024)
A Black Hole Quencher-3 (BHQ-3) derivative was synthesized through an azo-coupling reaction between Methylene Violet 3RAX and a tertiary aniline functionalized with a pendant primary amine, allowing subsequent peptide conjugation. The synthesized compounds were characterized using NMR, UV–vis absorption, fluorescence spectroscopy, and mass spectrometry. The spectral properties of a Cy5/BHQ-3 amine pair were investigated through titration experiments in PBS (pH 7.4). The results confirmed Förster Resonance Energy Transfer (FRET), along with additional dynamic quenching, as evidenced by the Stern–Volmer analysis. The Stern–Volmer constant (KSV) was determined to be 1.40 × 105 M−1. These findings confirm the potential of this system for use in molecular probes and bioimaging applications.